Spatial pattern of heavy metals accumulation risk in urban soils of Beijing and its influencing factors - Liu, Rui; Wang, Meie; Chen, Weiping; Peng, Chi (Environmental pollution (1987), 2016)
Accumulations of heavy metals in urban soils are highly spatial heterogeneity and affected by multiple factors including soil properties, land use and pattern, population and climatic conditions. We studied accumulation risks of Cd, Cu, Pb and Zn in unban soils of Beijing and their influencing based on the regression tree analysis and a GIS-based overlay model. Result shows that Zinc causes the most extensive soil pollution and Cu result in the most acute soil pollution. The soil's organic carbon content and CEC and population growth are the most significant factors affecting heavy metal accumulation. Other influence factors in land use pattern, urban landscape, and wind speed also contributed, but less pronounced. The soils in areas with higher degree of urbanization and surrounded by intense vehicular traffics have higher accumulation risk of Cd, Cu, Pb, and Zn. •Zn accumulations were the most extensive and Cu accumulations were the most acute.•Accumulations of Cd, Cu, Pb and Zn in urban soils were caused by different sets of influence factors.•Soil's organic carbon content and CEC and population growth were the most significant factors.•Accumulation risks were highly related with urbanization level and human activities. A combined approach of employing geographical information systems and regression tree analyses identify the potential risks of accumulation Cd, Cu, Pb, and Zn in urban soils according to soil properties, urban land use patterns, urban landscape, demographics, and microclimatic conditions.